2013
DOI: 10.1371/journal.pone.0068485
|View full text |Cite
|
Sign up to set email alerts
|

Human Gender Differences in the Perception of Conspecific Alarm Chemosensory Cues

Abstract: It has previously been established that, in threatening situations, animals use alarm pheromones to communicate danger. There is emerging evidence of analogous chemosensory “stress” cues in humans. For this study, we collected alarm and exercise sweat from “donors,” extracted it, pooled it and presented it to 16 unrelated “detector” subjects undergoing fMRI. The fMRI protocol consisted of four stimulus runs, with each combination of stimulus condition and donor gender represented four times. Because olfactory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 41 publications
2
40
1
Order By: Relevance
“…Those studies found that women and men showed different EEG activity under various conditions [32][33][34]. Radulescu and Mujica-Parodi [35] stated that women have a better olfactory sensation than men in many species and differences in their sensitivity may be based on biological meanings. Recently, Haehner et al [36] reported that women easily identified different fragrances (orange, lime, and lemon) and changed their behavior accordingly when compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies found that women and men showed different EEG activity under various conditions [32][33][34]. Radulescu and Mujica-Parodi [35] stated that women have a better olfactory sensation than men in many species and differences in their sensitivity may be based on biological meanings. Recently, Haehner et al [36] reported that women easily identified different fragrances (orange, lime, and lemon) and changed their behavior accordingly when compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…Rodent studies demonstrate that SFL in infant rats occurs through chemosignalling pathways [27, 33]. It has not been determined whether alarm chemosignaling plays a role in human infants, although recent studies suggest that olfaction may mediate social fear transmission in adults [72, 73]. Interestingly, research shows that infant SFL may occur without any increased activation of the ACC or the insular cortex which are not fully functional until later in life [33].…”
Section: The Ontogeny Of Sflmentioning
confidence: 99%
“…In mice, for example, some pheromone receptors may also be present in the main olfactory epithelium (Omura and Mombaerts 2014;Kanageswaran et al 2015), possibly explaining why some apparently pheromone-mediated behavior is maintained in species lacking the vomeronasal organ. Finally, the debate on whether humans are capable of detecting pheromones is still far from resolved, as anatomical advances are ongoing Wessels et al 2014;Vasuki et al 2016), and behavioral experiments suggest that we can perceive conspecific chemosensory cues (Radulescu and Mujica-Parodi 2013;Lübke and Pause 2015;Gelstein et al 2011). Finally, the debate on whether humans are capable of detecting pheromones is still far from resolved, as anatomical advances are ongoing Wessels et al 2014;Vasuki et al 2016), and behavioral experiments suggest that we can perceive conspecific chemosensory cues (Radulescu and Mujica-Parodi 2013;Lübke and Pause 2015;Gelstein et al 2011).…”
Section: Vomeronasal Lossmentioning
confidence: 99%
“…While Trpc2 has been pseudogenized in the harbor seal and river otter (Yu et al 2010), both species retain a well-developed main olfactory system and behavioral studies indicate the presence of some olfactory social communication (van Valkenburgh et al 2011;Stoffel et al 2015). Finally, the debate on whether humans are capable of detecting pheromones is still far from resolved, as anatomical advances are ongoing Wessels et al 2014;Vasuki et al 2016), and behavioral experiments suggest that we can perceive conspecific chemosensory cues (Radulescu and Mujica-Parodi 2013;Lübke and Pause 2015;Gelstein et al 2011).…”
Section: Vomeronasal Lossmentioning
confidence: 99%